Patient perceptions of schizophrenia in forensic and general adult psychiatry. Issue 3 (4th May 2017) - Wall, Emma L. E.; Mirfin, David; White, Sarah; Mezey, Gillian C.
Abstract: This study explores the illness perceptions of patients with schizophrenia in forensic settings and contrasts their views with those of a general adult psychiatry sample. It was hypothesised that forensic psychiatric patients would have more negative illness beliefs than general adult patients. A cross-sectional survey was used. Forty forensic patients and 32 general adult patients with schizophrenia were recruited. They completed the Illness Perception Questionnaire for Schizophrenia (IPQS), a valid and reliable measure of illness perceptions in mental health problems. Forensic patients perceived their illness to be less chronic, less cyclical, and had a lower negative emotional response to illness. Our results did not support our original hypothesis and possible reasons are explored. Acknowledging patient's views when formulating management plans could permit more effective individually tailored treatment.